THE IMPLEMENTATION OF BABY-FRIENDLY COMMUNITY INITIATIVE ON KENYA AND INDONESIA - Muhka, Reni; Huriah, Titih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Baby Friendly Community Initiative (BFCI) is one of the programs to improve the quality of care for mothers and babies in the community. One of BFCI's flagship programs is exclusive breastfeeding. This Literature Review aims to determine the implementation of BFCI programs in developing countries. The Literature Review follows PRISMA's reporting method. The database uses Science Direct, PubMed, Scopus, EBSCO and Google Scholar. The keyword uses "Baby-Friendly Community Initiative". The inclusion criteria are articles for the last five years (2017-2022) in English, full text, and research in developing countries. The exclusion criteria are review, only abstracts and books. Critical appraisal uses JBI as a research journal quality evaluation tool. Systematic analysis is used for synthesis results. The results found that Kenya and Indonesia implemented BFCI. The result of implementing BFCI in Kenya are that society has the potential to increase the level of exclusive breastfeeding for babies and has a positive impact on the practice of complementary feeding, whereas in Indonesia this is an increase in exclusive breastfeeding. The BFCI program can be implemented in Indonesia as a program to increase exclusive breastfeeding coverage with a community empowerment approach.